Insights to the functional relationships of Māori harvest practices: Customary use of a burrowing seabird. Issue 6 (12th June 2015) - Lyver, Phil O'B.; Jones, Christopher J.; Belshaw, Noti; Anderson, Alice; Thompson, Ray; Davis, Joe
ABSTRACT Indigenous peoples globally have relied on customary practices for safeguarding and optimizing harvest of wildlife populations, including seabirds. Increasingly, there have been efforts to engage these indigenous and local knowledge systems to inform responses to the global biodiversity crisis. We considered how customary harvest management as practiced historically by New Zealand Māori might have contributed to sustaining a burrowing seabird population. We used a deterministic age‐structured model of a population of grey‐faced petrels (Pterodroma gouldi). By harvesting pre‐fledging chicks, rather than adult birds, Māori harvesters had less of an impact on population growth rates; annual population growth rate dropped below 1.0 if 2% or more of adult birds were harvested compared with threshold harvests of 25% or more of either eggs or chicks. Restrictions such as prohibition of the digging out of burrows or the use of a snaring pole to catch chicks would lead to an annual harvest of less than our estimated deterministic threshold for a sustainable harvest of 25% of chicks even if all the chicks within arm's reach down the burrows were caught. The cultural practice of rotating harvests or resting populations was also effective; harvesting every 3 years allowed up to 75% of chicks to be taken without causing the theoretical population to decline. The development and implementation of ecologically meaningful but also culturally appropriate approaches to managing wildlife is an important part of efforts to de‐colonialize conservation management. We recommend adaptive or multi‐evidence‐based approaches where scientific information and methods complement indigenous knowledge and practices in the management of wildlife. © 2015 The Wildlife Society.